Sistematik Literatur Review : Hubungan Stres Terhadap Gangguan Muskuloskletal Pada Pekerja - Agustianti, Erika (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
"The work environment and individual work can cause musculoskeletal disorders. These disorders occur in body structures such as muscles, joints, tendons, ligaments, nerves, bones, and the local blood circulation system. In Indonesia, the prevalence of musculoskeletal diseases has reached 7.9% (Riskesdas, 2018). Stress and musculoskeletal disorders are the main causes of work-related illnesses. This study aims to determine the relationship between stress and musculoskeletal disorders in workers using a systematic literature review method. Secondary data originating from PubMed were utilized, employing the keywords 'MSDs', 'Work Stress', and 'worker' with "AND" as the Boolean operator. Nine articles meeting the inclusion and exclusion criteria were identified. The results of the literature review reveal a high prevalence of musculoskeletal disorders in various work sectors. These disorders are multifactorial, with work stress being a significant factor. The research findings clearly establish a relationship between work stress and musculoskeletal disorders. Recognizing risk factors for musculoskeletal disorders and identifying factors that cause work stress in workers are crucial steps for prevention. This can be achieved through regular evaluation of fatigue and psychological counseling for each worker, providing opportunities for workers to participate in education and training programs, and supporting communication between workers and management to actively resolve worker conflicts."